The early detection of reading difficulties - Clay, Marie M. (New Zealand : Heinemann, 1993)
Techniques for identifying children who, by six years of age, are having difficulty learning to read and procedures for an individual reading recovery programme.
Includes index.
Keywords: Reading disability; Reading